The effect of high-frequency oscillatory ventilator combined with pulmonary surfactant in the treatment of neonatal respiratory distress syndrome. Issue 32 (12th August 2022) - Wang, Tie-Yan; Zhu, Ying; Yin, Jia-Lin; Zhao, Li-Yan; Wang, Hai-Jun; Xiao, Chun-Wang; Wu, Li-Yan
Abstract : Objective: To investigate the efficacy of high-frequency oscillatory ventilation (HFOV) combined with pulmonary surfactant (PS) in the treatment of neonatal respiratory distress syndrome (NRDS). Methods: This study is a retrospective clinical study. Seventy-two NRDS neonates were selected as the subjects from November 2019 to November 2020, and divided into observation group (40 cases, HFOV treatment) and control group (32 cases, conventional mechanical ventilation treatment). All cases were treated with PS and comprehensive treatment. The therapeutic effect, arterial partial pressure of oxygen (PaO2 ), arterial partial pressure of carbon dioxide (PaCO2 ), Percentage of inhaled oxygen concentration (FiO2 ), mean arterialpressure, oxygenation index (OI), and complications were compared in the 2 groups. Results: The total effective rate of the observation group was 90.0%, significantly higher than that of the control group. After treatment, the observation group has higher PaO2 levels and lower levels of PaCO2, mean arterial pressure, FiO2, and OI than the control group. There was no significant difference in the incidence of complications between the 2 groups. Conclusion: HFOV combined with PS has a significant effect on NRDS, which can improve the arterial blood gas index without increasing the incidence of complications.